Effects of site preparation on physical and chemical properties as indicators of forest soil quality - Fonseca, Felícia; Figueiredo, Tomás de (Gaia Scientia, 2016)
Soil quality evaluation is an important tool to observe the sustainability of soil management practices. Therefore, an evaluation methodology was applied to seven sets of site preparation operations for forest stand installation (treatments), in order to assess their impacts on soil quality parameters. Treatments considered were (ranked from lowest to highest tillage intensity): (1) Original soil control (no intervention on the original abandoned field) (TSMO); (2) No subsoiling, no ploughing, plantation with hole digger (SMPC); (3) Subsoiling over the whole area, with covering shovel; (RCAV); (4) No subsoiling, contour bunds shaped by two plough passes (SRVC); (5) Subsoiling in future plantation rows, contour bunds shaped by two plough passes (RLVC); (6) Subsoiling over the whole area, contour bunds shaped by two plough passes (RCVC); (7) Subsoiling over the whole area, contour ploughing over the whole area (RCLC). These were applied in an experimental site near Macedo de Cavaleiros, NE Portugal, covering 1125 m2 each, further planted with a mixed stand (Douglas fir, Pseudotsuga mensiezii, and Chestnut, Castanea sativa). In each one of the treatments, 6 soil profiles were observed and sampled in the plantation row of the newly installed forest stand. Soil quality evaluation was done taking into account soil morphology features, soil analyses results at 0-20, 20-40 and 40-60 cm depth, and enrichment ratios of soil parameters computed with data of actual and undisturbed conditions. The treatments SRVC, RLVC and RCLC showed the highest depth with an increasing of 20 to 40 cm when compared with the original situation. Also the same treatments presented the highest values of carbon and nitrogen in the layer 20-40 cm, but the lowest in the surface soil layer. Generally, no significant differences were found among treatments in what concerns exchangeable bases and acidity, cation exchange capacity, base saturation and pH values. The amounts of finer particles tend to increase with tillage intensity and, on the contrary, the opposite trend was found for bulk density. For the studied conditions, the SRVC and RLVC treatments seem to be the most adequate set of site preparation operations for new plantations of forest stands.